Membagun Usaha Secara Digital / Online - Achmat Fikri Sallaby; Indra Kanedi; Siswanto Siswanto; Setiaji Ayu Handayani; Endah Puspaningrum (Jurnal Dehasen Untuk Negeri, 2024)
Based on reviews of the implementation of Community Service activities held in Hamlet II, Harapan Village, Pondok Kelapa District, Central Bengkulu Regency, residents are enthusiastic about understanding more about building digital/online businesses. Very big impact. So it is hoped that in the future these residents will be willing to implement and interact with each other to build digital businesses such as using e-business and e-commerce applications in Harpan Village, Pondok Coconut District, Central Bengkulu Regency, and be able to compete with the ability to guarantee that e-business meets the three key characteristics required. in any business transaction, validation, integrity and privacy encourage the adoption of digital technology which reduces cost efficiency and competition. This can be seen from the many questions asked by residents during the activity.